2012
DOI: 10.1557/mrs.2012.7
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development and physical infrastructure materials

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The results of this study are in line with research by (Heard et al, 2012), concluding that PDN has no effect on ROA. This can be explained that if management is careful in the sense that the source of foreign exchange funds is used to finance foreign exchange transactions or to minimize the risk can be overcome by hedging.…”
Section: Pdnsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study are in line with research by (Heard et al, 2012), concluding that PDN has no effect on ROA. This can be explained that if management is careful in the sense that the source of foreign exchange funds is used to finance foreign exchange transactions or to minimize the risk can be overcome by hedging.…”
Section: Pdnsupporting
confidence: 91%
“…The influence of the exchange rate on RSHM was examined by (Heard et al, 2012), stating that the exchange rate affected RSHM. (Ngoc et al, 2009) in the period of 1986-2006 when the liberalization of the forex market economy was implemented, showed that changes in currency exchange rates negatively affected the profitability of banking companies.…”
Section: The Influence Of Kurs On Rshmmentioning
confidence: 99%
“…This tremendous demand for resources has led to a growing concern about potential contributions to regional resource scarcity for concrete production 32 . In the United States from 1900 to 2000, a period of significant infrastructure development in the nation, the demand for crushed stone, sand, and gravel grew from being ~60% greater to being ~290% times greater than the sum of all other raw material flows used by human activities in that same time period 33 . Although sand and gravel are widely abundant on Earth 34 , they are usually not transported over long distances due to the economic cost of transporting such heavy materials 35,36 .…”
Section: Regional Resource Scarcitymentioning
confidence: 99%
“…This is deemed by and large because of the concrete production (Mora, 2007). Concrete is the most commonly used building material in infrastructure and building projects (Heard et al , 2012). Annually, over 2.5 tons of concrete is used on average per person in a year and is projected to increase (Lippiatt and Ahmad, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As an example for recycling, concrete debris can be diverted from landfills to produce aggregates after being crushed, graded and washed (McIntyre et al , 2009; Poon et al , 2004). Incorporation of materials such as slag, fly ash and pozzolans from the waste streams of other industries in concrete production, either in part or in whole, can also considerably reduce waste generation and energy consumption (Heard et al , 2012). Another strategy involves utilizing cementitious materials derived from biological sources, such as microorganisms and plants to manufacture bioconcrete.…”
Section: Introductionmentioning
confidence: 99%